MACRO AND MICRONUTRIENTS REGIMES IMPACT GROWTH DYNAMICS OF Lilium L. LA HYBRID BULBLETS - Iqra Summan; Iftikhar Ahmad; Muhammad Usman; Irfan Afzal (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: SimSun; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Lilium, a member of family Liliaceae, is among top ten highly demanded geophytic cut flowers in global markets; and during recent years, its demand has increased several folds in local markets as well. However, quality bulb production of lilium in different regions of the world is a major limiting factor and<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: SimSun; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> nutrients for best quality bulb production needs to be optimized.<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: SimSun; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Therefore, a study was conducted to evaluate the efficacy of various macro and micronutrients on bulblet growth and bulb development of Lilium L. LA hybrid cv. ‘Indian Summerset’. <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: GaramondPremrPro; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Treatments included<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: SimSun; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">no additional nutrient application (control), nitrogen (N) (123.5 kg ha-1), phosphorous (P) (148.2 kg ha-1), potassium (K) (148.2 kg ha-1), nitrogen + phosphorous (NP) (123.5:148.2 kg ha-1), nitrogen + potassium (NK) (123.5:148.2 kg ha-1), phosphorous + potassium (PK) (148.2:148.2 kg ha-1), nitrogen + phosphorous + potassium (NPK) (123.5:148.2:148.2 kg ha-1), nitrogen + phosphorous + potassium + secondary elements (NPK + SE) (CaSO4 (Ca) @ 61.75 kg ha-1, MgSO4 (Mg) @ 1.23 kg ha-1, and Sulphur (S) @ 2.5 kg ha-1), nitrogen + phosphorous + potassium + <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">micronutrients (NPK+ Micro) (ZnSO4 (Zn) @ 12.35 kg ha-1, FeSO4 (Fe) @ 2% solution and boric acid (B) @ 2% solution) and nitrogen + phosphorous + potassium + secondary nutrients + micronutrients (NPK + SE + Micro).<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> All treatments were replicated three times with 20 bulblets in each replicate, which were laid out in a randomized complete block design.<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: SimSun; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Application of various nutrients exhibited <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">statistically significant differences regarding various growth and development attributes.<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Plants supplemented with NPK + SE + Micro produced statistically improved weight <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(34.4 g) <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">and diameter <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(36.4 mm) <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">of bulblets. <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Plants supplemented with NPK + SE + Micro exhibited <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">significantly<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> higher photosynthetic rate, transpiration rate, stomatal conductance and sub stomatal CO2. Highest leaf SPAD values, greatest leaf N, Mg and S contents were recorded in plants treated with NPK + S.E. Highest leaf P, K,<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ca and Zn contents were recorded in plants supplemented with NPK + SE + Micro. Plants fertilized with NPK + Micro produced greatest leaf area and Fe contents.<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Plants deficit in nutrients exhibited poor growth and bulb development<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. It is concluded that <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">exogenous<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 106%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> application of NPK+ SE + Micro produced superior quality Lilium LA hybrid ‘Indian Summerset’ bulbs compared to other nutrient regimes. Growers and bulb producers may use NPK + SE + Micro in combined form for commercial cultivation and bulb production of Lilium LA hybrid.
Keywords: Bulb production; cut flowers; geophytes; primary nutrients; secondary elements; micronutrients.